2018
DOI: 10.2298/abs180309022g
|View full text |Cite
|
Sign up to set email alerts
|

Leaf micromorphology, antioxidative activity and a new record of 3-deoxyamphoricarpolide of relict and limestone endemic Amphoricarpos elegans Albov (compositae) from Georgia

Abstract: We examined for the first time the leaf micromorphology, phytochemistry and biological activity of the rare and stenoendemic Amphoricarpos elegans Albov (Compositae) from Georgia. Scanning electron microscopy (SEM) revealed the presence of glandular trichomes on the leaves, which appeared as glandular dots that are considered the main sites of biosynthesis and accumulation of sesquiterpene lactones. Using high-performance liquid chromatography (HPLC) and nuclear magnetic resonance (NMR) spectroscopy analyses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Regarding glandular trichomes of G. pulchella, Bartoli et al (2011) showed that the secretion is accumulated between the cell wall and the cuticle, which released the secretion when it breaks. It is documented that the secretion, of both, canals and trichomes, is composed of essential oils, lipids, sesquiterpene lactones, resins, pectinlike substances, alkaloids, flavonoids and tannins Pais 1987, 1988;Pagni et al 2003;Andreucci et al 2008;Lusa et al 2016;Gavrilović et al 2018a). Stem anatomy of the examined species could be considered as typical for the Asteraceae (Metcalfe and Chalk 1957) and is in accordance with previously described in the papers of Konowalik and Kreitschitz (2012) and Ivănescu et al (2015) who studied anatomy of A. absinthium.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Regarding glandular trichomes of G. pulchella, Bartoli et al (2011) showed that the secretion is accumulated between the cell wall and the cuticle, which released the secretion when it breaks. It is documented that the secretion, of both, canals and trichomes, is composed of essential oils, lipids, sesquiterpene lactones, resins, pectinlike substances, alkaloids, flavonoids and tannins Pais 1987, 1988;Pagni et al 2003;Andreucci et al 2008;Lusa et al 2016;Gavrilović et al 2018a). Stem anatomy of the examined species could be considered as typical for the Asteraceae (Metcalfe and Chalk 1957) and is in accordance with previously described in the papers of Konowalik and Kreitschitz (2012) and Ivănescu et al (2015) who studied anatomy of A. absinthium.…”
Section: Discussionsupporting
confidence: 87%
“…One of the largest angiosperm family, Asteraceae, includes hundreds of species of economic interest, e.g., medicinal plants which are used therapeutically, and consequently, their anatomy and morphology have been studied, including the structures which produce and storage specialized metabolites (Werker and Fahn 1981;Ascensão and Pais 1987;Figueiredo and Pais 1994;Ascensão et al 2001;Andreucci et al 2008;Simpson 2009;Camilotti et al 2014;Gavrilović et al 2016). These secretory structures in Asteraceae could be found in the form of glandular trichomes, cavities, canals, laticifers, hydathodes, idioblasts and glandular appendices (Metcalfe and Chalk 1950;Carlquist 1958;Lestern and Curtis 1985;Castro et al 1997;Gavrilović et al 2018a). In addition, an importance of these structures in taxonomic studies was emphasized by some authors (Solereder 1908;Metcalfe andChalk 1950, 1979;Metcalfe 1983), with the main purpose of distinguishing orders, tribes, genera and even certain species, because various secretory structures may be found in a different parts of the same plant or be only located in certain plant organs.…”
Section: Introductionmentioning
confidence: 99%
“…According to Robinson (2009) the presence of glandular trichomes of the short-stalked capitate type is a widely distributed microcharacter in Asteraceae. Biseriate trichomes are very common within the family (Gavrilović et al 2018(Gavrilović et al , 2019. Glandular trichomes are found in other Centaurea species (Rusak et al 1992, Luković et al 2013, Haratym et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Glandular trichomes are found in other Centaurea species (Rusak et al 1992, Luković et al 2013, Haratym et al 2020). These trichomes are the main sites of production and accumulation of sesquiterpene lactones (Gavrilović et al 2018). Cnicin, a biologically active sesquiterpene lactone, has been reported as a constituent of C. glaberrima (Tešević et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that cypsela features are very informative at the generic level within the Xerantheminae (Gavrilović et al 2019). In a previous investigation, we examined leaf micromorphology of A. elegans and its relationship with production of sesquiterpenes lactones and antioxidative activity (Gavrilović et al 2018a). The morpho-anatomical study of A. elegans done by Petit (1977) represents a valuable contribution to knowledge about the micromorphology of this species, but it lacks SEM micro-graphs.…”
Section: Introductionmentioning
confidence: 99%